THE IMPORTANCE OF INDUSTRIAL PROPERTY RIGHTS IN THE BUSINESS SECTOR (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The subject- matter of this research is the role and significance of industrial property rights for the establishment, economic growth and development of companies. In circumstances when the business sector finally understood the meaning and role of industrial property rights, the questions of their role and meaning in starting a specific business venture, their role as capital in the company, and the need for their protection, arose naturally and logically.Today, we witness numerous and heterogeneous court and arbitration disputes concerning the question, whether a certain "creation of the mind" can be brought under the legal regime of "industrial property rights", and how they can be protected. Only a superficial analysis of this problem is enough to determine that from the aspect of protection and notion, this issue is becoming more and more complex.In this paper, we will focus on the role of industrial property rights in the establishment and economic progress of companies, as well as on the question of what is the value of industrial property rights as capital in the company.In order to achieve the main goal of this research, we will use several methods, the most prominent of which are: the analytical-description method, the summary and analysis method, the comparative method, and finally, in the conclusion section, we will use the method of induction and deduction.
Keywords: company, trademark, industrial design, business venture, protection.